A Correlational Study: Grammar Proficiency and Reading Comprehension of Descriptive Text in MTs Mathlaul Anwar Bakung - Muhtadi, Muhtadi; Gumelar, Rizki Elang; Sudirman, Ade; Mujani, Sahril (FKIP UNISKA, 2024)
The research explored the correlation between proficiency in grammar and the comprehension of descriptive text within a group of 60 eighth-grade students in MTs Mathlaul Anwar Bakung. between proficiency in grammar and reading comprehension. These results suggest that improving students' grammar proficiency may contribute to better understanding of descriptive text, but other factors should also be considered in order to enhance overall comprehension skills. Additionally, further research is needed to explore the specific factors that may influence reading comprehension of descriptive text in order to develop comprehensive strategies and interventions.